2007
DOI: 10.1007/s10741-007-9062-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of insulin-regulated aminopeptidase in the effects of the renin–angiotensin fragment angiotensin IV: a review

Abstract: For decades, angiotensin (Ang) II was considered as the end product and the only bioactive peptide of the renin-angiotensin system (RAS). However, later studies revealed biological activity for other Ang fragments. Amongst those, Ang IV has drawn a lot of attention since it exerts a wide range of central and peripheral effects including the ability to enhance learning and memory recall, anticonvulsant and anti-epileptogenic properties, protection against cerebral ischemia, activity at the vascular level and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 248 publications
(154 reference statements)
5
79
0
Order By: Relevance
“…Despite accumulating evidence of Ang IV action through insulin-regulated aminopeptidase, our results also support the notion that several Ang IV physiological effects could be mediated through AT1-R. 11,45,46 Hence, depending on its concentration in physiological or pathophysiological situations, Ang IV can act as an efficient AT1-R agonist. Of note, Ang IV, which lacks the first 2 N-terminal amino acids of Ang II (Table S2), is sufficient for producing full agonism on both G-protein and β-arr recruitment, in line with previous structure/function studies.…”
Section: Galandrin Et Al Angiotensin-(1-7) Is a Biased Ligand At At1-supporting
confidence: 71%
“…Despite accumulating evidence of Ang IV action through insulin-regulated aminopeptidase, our results also support the notion that several Ang IV physiological effects could be mediated through AT1-R. 11,45,46 Hence, depending on its concentration in physiological or pathophysiological situations, Ang IV can act as an efficient AT1-R agonist. Of note, Ang IV, which lacks the first 2 N-terminal amino acids of Ang II (Table S2), is sufficient for producing full agonism on both G-protein and β-arr recruitment, in line with previous structure/function studies.…”
Section: Galandrin Et Al Angiotensin-(1-7) Is a Biased Ligand At At1-supporting
confidence: 71%
“…38 Additional studies have demonstrated that AngIV (which is produced via AngII degradation) has both anticonvulsant and antiepileptic effects. 39 In a previous study, we found evidence of upregulation of ACE and of the AT 1 receptor in the hippocampi of WARs with TLE, and we showed that blockage of the AT 1 receptor by systemic administration of the antagonist losartan significantly decreased the severities of seizures, therefore suggesting a key role for AngII. 28 Nevertheless, as described above, we surprisingly found Ang-(1-7) to be the main metabolite generated after AngI degradation, whereas AngII formation was not detected.…”
Section: Downloaded Frommentioning
confidence: 48%
“…21,22 Some of the effects of AngIV may be mediated by an interaction with AT1R and/or AT2R, or by a mixture of all three receptors (AT1R, AT2R, IRAP), possibly depending on tissue type and expression pattern. 22 Thus, the present results cannot exclude the possibility that the effects of AngIV are mediated via the AT2R in line with our previous work showing that AT2R activation increased the glucose-induced electrogenic response in a similar setting. 14 Pharmacological analyses using stable and highly selective AngIV analogs that have been developed should considerably improve the outcomes of future studies.…”
Section: Discussionmentioning
confidence: 99%